1998
DOI: 10.2110/jsr.68.487
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary processes at the base of a West Antarctic ice stream; constraints from textural and compositional properties of subglacial debris

Abstract: Samples of sediments from beneath Ice Stream B (at camp UpB), West Antarctica, provide the first opportunity to study the relationship between sediment properties and physical conditions in a sub-ice-stream environment. Piston coring in holes bored by hot-water drilling yielded five 1-3 m long, undisturbed subglacial sediment cores. We analyzed granulometry, composition, and particle morphology in these cores. The UpB cores are composed of a clay-rich, unsorted diamicton containing rare marine diatoms. Sedimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
167
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(184 citation statements)
references
References 76 publications
11
167
0
Order By: Relevance
“…A maximum Dt RMS = 43 ms observed at an offset of 11,500 m, which is approximately 0.85% of the total travel time, while most of the residuals are less than 10 ms. Studinger et al, 2001]. Several authors have also placed emphasis on the close tie between the onset of streaming ice flow and a step in subglacial topography [McIntyre, 1985;Joughin et al, 1999;Hulbe et al, 2000], and our results are in agreement with this interpretation, revealing an indirect influence of subglacial topography on the initiation of streaming ice flow along the upper reaches of ice streams C and D. Seismic evidence points to depressions in bedrock topography that have been filled by subglacial sediments, probably from marine deposition in a preglacial setting [Scherer et al, 1998;Tulaczyk et al, 1998]. Ice flow velocity increase in the flow direction of C1B occurs with no identifiable step in bed topography (Figure 5), and the enhanced velocity of ice stream D occurs over a subtle low in basal topography (Figure 6).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…A maximum Dt RMS = 43 ms observed at an offset of 11,500 m, which is approximately 0.85% of the total travel time, while most of the residuals are less than 10 ms. Studinger et al, 2001]. Several authors have also placed emphasis on the close tie between the onset of streaming ice flow and a step in subglacial topography [McIntyre, 1985;Joughin et al, 1999;Hulbe et al, 2000], and our results are in agreement with this interpretation, revealing an indirect influence of subglacial topography on the initiation of streaming ice flow along the upper reaches of ice streams C and D. Seismic evidence points to depressions in bedrock topography that have been filled by subglacial sediments, probably from marine deposition in a preglacial setting [Scherer et al, 1998;Tulaczyk et al, 1998]. Ice flow velocity increase in the flow direction of C1B occurs with no identifiable step in bed topography (Figure 5), and the enhanced velocity of ice stream D occurs over a subtle low in basal topography (Figure 6).…”
Section: Discussionsupporting
confidence: 90%
“…The black dashed box to the top of the map is the location of the aerogeophysical survey of Bell et al [1998], and the white dashed line is the seismic refraction study of Anandakrishnan et al [1998]. The study region of Studinger et al [2001] covers most of this map, and the aerogeophysical survey of Blankenship et al [2001] covers the catchments of ice streams B and C. Other seismic and borehole experiments performed along the Siple Coast are located closer to the grounding line along the ice streams Rooney et al, 1987aRooney et al, , 1987bRooney et al, , 1991Engelhardt et al, 1990;Munson and Bentley, 1992;Engelhardt and Kamb, 1998;Tulaczyk et al, 1998;Kamb, 2001].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For ex am ple, rapid move ment of Ice Stream B in West Antarctica was ini tially at trib uted to the pres ence of thick, un con sol i dated, strongly sat u rated de formed de pos its at the ice sheet base (Alley et al, 1986(Alley et al, , 1987, but sub se quent stud ies have shown that the basal move ment of the ice stream is con cen trated within only a very thin layer of sub strate (cf. Engelhardt and Kamb, 1998;Tulaczyk et al, 1998). Brown et al (1987) pointed out that the Puget Lobe of the Pleis to cene Cordilleran Ice Sheet moved mainly by slid ing and that only lo cal de for ma tion was caused by clasts plough ing the sub strate.…”
Section: Introductionmentioning
confidence: 99%